RADIOFREQUENCY TURBINATE REDUCTION IMPROVE QUALITY OF LIFE TURBINATE HYPERTROPHY PATIENTS - Arum Kartikadewi; Wahyu Budi Martono; Ratri Cahyaningtyas (Universitas Muhammadiyah Semarang, 2017)
Turbinate Hypertrophy decreases quality of life due to nasal obstructions symptom. Radiofrequency turbinate reduction is minimal invasive surgical that expected to maintain nasalfunction. The surgical procedure compromises the improvement of patients‟ quality of life. There is nocurrent consensus the difference quality of life before and after the procedure. Cross-sectonal design was done in 31 turbinate hypertrophy patients with radiofrequency turbinate reduction. Before and after the procedure, patient‟s quality of life was assessed using a sinonasal outcome test-22 (SNOT-22) questionnaire parameters. Questionnaire SNOT-22 scores before and after the procedure was analyzed by t-dependent test. Patients characteristic was 20-39 years old age, employed, has past allergic rhinitis. Mean of SNOT-22 total score before procedure was 60.35 + 7,264 and the mean postoperative total score was 10.19 + 3,103. There were significant differences between quality of life before and after radiofrequency turbinate reduction ( p <0.0001). The better improvement symptom are nasal-throat symptom (4-79 %), head, ear and face symptom (2,6-6,4%), diminish sleep disturbance (58,6-71,6%),disturbance activity reduce 57,4-72,8%, and physicological stress reduce 2-25,8%. Radiofrequencyturbinate reduction improve the quality of life turbinate hypertrophy patients Keywords : Turbinate hypertrophy, Turbinate reduction radiofrequency, SNOT-22